Attitude and beliefs about the social environment associated with chemsex among MSM visiting STI clinics in the Netherlands: An observational study. - Ymke J Evers; Jill J H Geraets; Geneviève A F S Van Liere; Christian J P A Hoebe; Nicole H T M Dukers-Muijrers (PLoS ONE, 2020)
BACKGROUND:Drug use during sex, 'chemsex', is common among men who have sex with men (MSM) and related to sexual and mental health harms. This study assessed associations between chemsex and a wide range of determinants among MSM visiting STI clinics to increase understanding of characteristics and beliefs of MSM practicing chemsex. METHODS:In 2018, 785 MSM were recruited at nine Dutch STI clinics; 368 (47%) fully completed the online questionnaire. All participants reported to have had sex in the past six months. Chemsex was defined as using cocaine, crystal meth, designer drugs, GHB/GBL, ketamine, speed or XTC/MDMA during sex in the past six months. Associations between chemsex and psychosocial determinants, socio-demographics, sexual behaviour and using tobacco or alcohol were assessed by multivariable logistic regression analyses. RESULTS:Chemsex was reported by 44% of MSM (161/368) and was not associated with socio-demographics. Independent determinants were 'believing that the majority of friends/sex partners use drugs during sex' (descriptive norm) (aOR: 1.95, 95%CI: 1.43-2.65), 'believing that sex is more fun when using drugs' (attitude) (aOR: 2.06, 95%CI: 1.50-2.84), using tobacco (aOR: 2.65, 95%CI: 1.32-5.32), multiple sex partners (aOR: 2.69, 95%CI: 1.21-6.00), group sex (aOR: 4.65, 95%CI: 1.54-14.05) and using online dating platforms (aOR: 2.73, 95%CI: 1.13-6.62). CONCLUSION:MSM are likely to find themselves in distinct social networks where it is the norm to use drugs when having sex and pleasure is linked to chemsex. Health services should acknowledge the social influence and pleasurable experiences to increase acceptability of strategies aimed at minimizing the possible harms of chemsex.